2014
DOI: 10.1186/1745-6215-15-443
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy as a novel treatment for halitosis in adolescents: study protocol for a randomized controlled trial

Abstract: BackgroundHalitosis is a common problem that affects a large portion of the population worldwide. The origin of this condition is oral in 90% and systemic in 10% of cases. The unpleasant odor is mainly the result of volatile sulfur compounds produced by Gram-negative bacteria. However, it has recently been found that anaerobic Gram-positive bacteria also produce hydrogen sulfide (H2S) in the presence of amino acids, such as cysteine. Light, both with and without the use of chemical agents, has been used to ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 49 publications
1
31
0
3
Order By: Relevance
“…The report of bad breath occurs most commonly after waking up, a transient physiological condition resulting from the reduced salivary flow during sleep [7]. Persistent halitosis can be caused by intraoral factors, such as oral diseases (periodontal disease, gingivitis, caries, biofilm accumulation and tongue coating) [4,7] as well as extraoral factors, such as systemic diseases (upper and lower respiratory tract infection, gastrointestinal disorders, metabolic diseases affecting the kidneys and liver, and endocrine disorders such as diabetes mellitus) [1,4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The report of bad breath occurs most commonly after waking up, a transient physiological condition resulting from the reduced salivary flow during sleep [7]. Persistent halitosis can be caused by intraoral factors, such as oral diseases (periodontal disease, gingivitis, caries, biofilm accumulation and tongue coating) [4,7] as well as extraoral factors, such as systemic diseases (upper and lower respiratory tract infection, gastrointestinal disorders, metabolic diseases affecting the kidneys and liver, and endocrine disorders such as diabetes mellitus) [1,4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The malodor originates from volatile sulfur compounds (VSC), i.e., hydrogen sulfate (H2S), methyl mercaptan (CH3SH) and dimethyl sulfate [(CH3)2S] [1,2,7,8,10], which are produced by gram-negative bacteria present in the oral cavity [7,8,10]. In addition, previous in vitro studies have shown that gram-positive bacteria such as Peptostreptococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The quantitative wound bioluminescence data are presented in Figure 7a. 3,13,21,22,47,48,49,50,51,52,59 …”
Section: Results and Discusssionmentioning
confidence: 99%
“…13,17 White coated tongue (CT), also known as a hairy tongue, is a consequence of the elongation and retention hyperkeratosis of the filiform papillae. [34][35][36] Causes of papillae hypertrophy may include poor oral hygiene, certain dietary habits, xerostomia due to dehydration, smoking or excessive use of alcohol. It is frequently accompanied by halitosis.…”
Section: F I G U R Ementioning
confidence: 99%
“…In some cases, it may indicate an oral yeast infection. [34][35][36] The coated tongue condition is found in up to 28% of the adult population as reported by different studies. 34,36 In our study, CT was present in 31% of the psoriatic patients and we found a significant difference between groups with an extremely large effect of psoriasis on their quality of life compared with the groups with no effect according to DLQI questionnaire.…”
Section: F I G U R Ementioning
confidence: 99%